When \(x^3 - x^2 = x^2(x - 1)\) you divided by zero.
–
Sharky Kesa
·
2 years, 8 months ago

Log in to reply

\((x-1)\) is equal to \(-1\), not \(0\). This is because you multiplied the \(x^3\) factor to get \(0\), meaning that \(1\ne0\).
–
Michael Diao
·
2 years, 8 months ago

Log in to reply

till x^2(x-1) =0 everything is right
but on next step there is mistake.
if ab=0 , a or b is 0 .Here a=x^2,b=(x-1).We already have a=0 which results in (x-1) may or may not equal to zero.To make the equation correct,(x-1) not equal to zero
–
Shaheed Vh
·
2 years, 8 months ago

## Comments

Sort by:

TopNewestWhen \(x^3 - x^2 = x^2(x - 1)\) you divided by zero. – Sharky Kesa · 2 years, 8 months ago

Log in to reply

\((x-1)\) is equal to \(-1\), not \(0\). This is because you multiplied the \(x^3\) factor to get \(0\), meaning that \(1\ne0\). – Michael Diao · 2 years, 8 months ago

Log in to reply

till x^2(x-1) =0 everything is right but on next step there is mistake. if ab=0 , a or b is 0 .Here a=x^2,b=(x-1).We already have a=0 which results in (x-1) may or may not equal to zero.To make the equation correct,(x-1) not equal to zero – Shaheed Vh · 2 years, 8 months ago

Log in to reply